Usefulness of intrauterine insemination in unexplained and male subfertility with mild form of oligoastheno teratozospermia (Journal of Dhaka National Medical College & Hospital, 2023)
Background: Unexplained infertility is a diagnosis of exclusion after systematic evaluation fails to identify a cause. Oligospermia is defined traditionally by a sperm density